A new energy electric car sound insulation material and its production process
The existing separator is solved by blending butyl rubber with crosslinked silicone rubber in sound insulation materials and combining grafting reaction of acrylonitrile-butadiene-styrene copolymer with silane coupling agent-modified silica The problem of poor barrier effect of acoustic materials at low frequency noise significantly improves the damping performance of the material and the dissipation effect of low frequency noise.
Patent Information
- Application Number
- CN202410440890.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-12
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-04-12
AI Technical Summary
The sound insulation materials prepared by existing multiphase composite technology have poor low-frequency noise barrier effects.
Butyl rubber is blended with crosslinked silicone rubber, and is treated by vulcanization and peroxide, and grafting reaction of acrylonitrile-butadiene-styrene copolymer and silane coupling agent to modify silica to form a modified silicone rubber and nanocomposite materials.
It significantly improves the dissipation and damping performance of the material under low-frequency noise, enhances the consumption capacity of vibration energy, and improves the overall performance of sound insulation materials.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sound insulation materials, and in particular to a sound insulation material for a new energy electric car and a production process thereof. Background Art
[0002] With the increasing demand for driving, the automotive industry has gradually become an indispensable and important part of modern industry. The comfort of a car is a comprehensive issue, which is mainly related to vibration, noise and acoustic roughness. When choosing a car, people pay more attention to the comfort of the car. Major OEMs have done a lot of work in the automotive related direction, such as improving the structure of parts, improving the level of assembly process, increasing vehicle strength and improving vibration frequency distribution, etc.; of course, more shock-absorbing, noise-reducing and sound-insulating materials are used. Vibration and noise have different propagation paths and different control methods, but they can all be handled by using shock-absorbing and noise-reducing materials. Automobile noise reduction and sound insulation materials include sound insulation materials, heat insulation materials, shock-absorbing materials and buffer materials, etc. These materials reduce the noise inside and outside the vehicle through various methods such as sound absorption, sound insulation and vibration reduction.
[0003] Polymer materials are functional materials based on polymers. Compared with other sound insulation materials, polymer materials have the advantages of light weight and easy processing. Due to their viscoelasticity, when subjected to alternating external forces, strain will lag behind stress, and there is a hysteresis phenomenon. In each cycle, mechanical dissipation will occur and energy will be consumed, that is, internal friction will be generated, thereby playing a damping effect. It can convert the vibration generated during the driving of the car into heat energy and can be used as a vibration reduction material. In order to give full play to the advantages of polymer materials and enhance their sound insulation effect, composite sound insulation materials based on polymers have been developed in recent years. This type of material adopts a multi-phase composite material system to form a multi-interface structure with different densities inside the material, which makes it have many advantages such as light weight, good processing performance, and corrosion resistance. However, similar to most polymer materials, the sound insulation frequency band of the sound insulation material prepared by multi-phase composite technology is still concentrated in the medium and high frequency area (500-5000Hz), and the blocking effect on low-frequency noise is not good. Summary of the invention
[0004] The purpose of the present invention is to provide a new energy electric car sound insulation material and a production process thereof to solve the following technical problems:
[0005] The sound insulation frequency band of the sound insulation materials prepared by the existing multi-phase composite technology is still concentrated in the medium and high frequency area, and the blocking effect on low-frequency noise is not good.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A production process of a new energy electric car sound insulation material comprises the following steps:
[0008] S1: After adding butyl rubber to the roller of a rubber mixer, adding stearic acid and zinc oxide for mixing, adding cross-linked silicone rubber for uniform mixing, adding diisopropyl peroxide, thinning out sheets, vulcanizing and forming, and obtaining modified silicone rubber; after mixing the modified silicone rubber and benzoyl peroxide, obtaining a mixed component;
[0009] S2: plasticizing the acrylonitrile-butadiene-styrene copolymer and rolling it, adding the mixed components and mixing them to obtain a masterbatch;
[0010] S3: Evenly mix the masterbatch and acrylonitrile-butadiene-styrene copolymer, melt-extrude, granulate, and dry to obtain a sound insulation material.
[0011] As a further embodiment of the present invention: the mass ratio of butyl rubber, stearic acid, zinc oxide, cross-linked silicone rubber, diisopropyl peroxide and benzoyl peroxide in S1 is 50-100: 1-3: 1-5: 120: 0.5-2.5: 2.4-3.6.
[0012] As a further solution of the present invention: the mass ratio of the acrylonitrile-butadiene-styrene copolymer and the mixed components in S2 is 1:1-1.2.
[0013] As a further solution of the present invention: the mass ratio of the masterbatch to the acrylonitrile-butadiene-styrene copolymer in S3 is 1:4-8.
[0014] As a further solution of the present invention: the specific steps of plasticizing the rollers in S2 are: setting the temperature of the open mill to 150-180°C for the front roller and 150-180°C for the rear roller, and adding acrylonitrile-butadiene-styrene copolymer between the two rollers to plasticize the rollers.
[0015] As a further embodiment of the present invention: the preparation method of the cross-linked silicone rubber comprises the following steps:
[0016] A1: Add methyl vinyl phenyl silicone rubber and chloroform into reaction kettle A, stir and dissolve, add m-chloroperbenzoic acid, keep warm at room temperature for 48-64 hours, wash and dry to obtain component 1;
[0017] A2: Add component 1, thioglycolic acid and acid anhydride into reactor B and disperse evenly, add concentrated sulfuric acid, control the temperature at 30-35°C, keep warm for 1-3h, wash and dry, and obtain component 2;
[0018] A3: Add nano-silicon dioxide, anhydrous ethanol and deionized water into reactor C and disperse them evenly, control the temperature at 60-70°C, add 3-(methacryloyloxy)propyltrimethoxysilane, adjust the pH to 3-5, keep the reaction warm for 1-3h, wash and dry to obtain component three;
[0019] A4: Add component 2, component 3 and chloroform into reactor D and disperse them evenly. Add triethylamine and react at room temperature for 1-3 hours. Wash and dry to obtain cross-linked silicone rubber.
[0020] As a further solution of the present invention: the addition ratio of methylvinylphenyl silicone rubber, chloroform and m-chloroperbenzoic acid in A1 is 1 g: 30-100 mL: 0.4-0.8 g.
[0021] As a further solution of the present invention: Component 1, thioglycolic acid and acid anhydride in A2 are added to a reaction kettle and dispersed evenly, and concentrated sulfuric acid is added in a ratio of 1 g: 5-10 mL: 2-5 mL: 0.01-0.02 mL.
[0022] As a further solution of the present invention: the addition ratio of nano silicon dioxide, anhydrous ethanol, deionized water, and 3-(methacryloyloxy)propyltrimethoxysilane in A3 is 10 g: 100-200 mL: 30-50 mL: 2-5 g.
[0023] As a further solution of the present invention: the addition ratio of component 2, component 3, chloroform and triethylamine in A4 is 1g: 0.1-0.3g: 10-100mL: 0.01-0.015g.
[0024] A new energy electric car sound insulation material is made by any of the above production processes.
[0025] Beneficial effects of the present invention:
[0026] (1) This application uses methyl vinyl phenyl silicone rubber as a matrix, firstly uses m-chloroperbenzoic acid to react with the carbon-carbon double bond of methyl vinyl phenyl silicone rubber for epoxidation to obtain component one; then uses the epoxy group on the molecular chain of component one to react with thioglycolic acid to open the ring, and connects the mercapto group on the silicone rubber molecular chain to obtain component two; finally, uses the mercapto group on the silicone rubber molecular chain to react with silica modified by a silane coupling agent to perform a click reaction under the catalysis of triethylamine to obtain a cross-linked silicone rubber. This application blends butyl rubber with cross-linked silicone rubber, and uses peroxide for vulcanization, and alloys the butyl rubber with the cross-linked silicone rubber to obtain a modified silicone rubber.
[0027] The present application utilizes a silane coupling agent to modify silica, imparts carbon-carbon double bonds to the surface of silica, and utilizes a click reaction between the surface functional groups of silica and the thiol groups of the silicone rubber side chains to organically connect silica and silicone rubber, one having a lower glass transition temperature and relatively flexible molecular segments, and the other having a higher glass transition temperature and difficult segment movement, and chemically grafts inorganic particles onto polymer chains as side chains, thereby increasing the number or polarity of side chains, and when they receive external force, the side chains generate relative movement and internal friction, thereby converting vibration energy into heat energy, increasing the cohesive energy of the system, and simultaneously adding monomers with functional groups is beneficial to cross-linking between polymer chains, thereby increasing the damping factor of silicone rubber.
[0028] The present application adds modified silicone rubber to acrylonitrile-butadiene-styrene copolymer, and the C=C double bonds obtained by modifying the surface of silica with a silane coupling agent are polymerized with the active groups or double bonds in the molecular chain of the acrylonitrile-butadiene-styrene copolymer. The silica modified with the silane coupling agent is used as a "bridge" to graft the acrylonitrile-butadiene-styrene copolymer and the silicone rubber, so that the mutual entanglement and interlacing of the cross-linked network of the organic molecular chains produce forced miscibility and synergistic effects, so that the material has the characteristics of homogeneity in the macroscopic sense and phase separation in the microscopic sense. The modified silicone rubber has a good dissipation effect on low-frequency noise, improves the loss factor of the material within the use range, increases the consumption of vibration energy, and significantly improves the damping performance of the material, thereby obtaining a nano-composite material with high damping and a wide temperature range. Reversible hydrogen bonding is formed between acrylonitrile-butadiene-styrene copolymer and silane coupling agent modified silica, resulting in weak interface friction. When subjected to external vibration, some hydrogen bonds will break or weaken, while new hydrogen bonds will be generated. This process converts mechanical energy into thermal energy, thereby obtaining high damping performance. In addition, the present application adds silane coupling agent modified silica as a reinforcing agent during the preparation of cross-linked silicone rubber to enhance the physical and mechanical properties of the base silicone rubber.
[0029] (2) This application uses methyl vinyl phenyl silicone rubber as the damping rubber. The main chain of methyl vinyl phenyl silicone rubber is Si-O-Si, and the chemical bond energy is high, so it has excellent heat resistance and weather resistance. The main chain of Si-O-Si molecule is helical, which gives the high damping silicone rubber good compression resilience. The side groups are methyl, phenyl and vinyl groups, which are arranged alternately along the main chain, giving the high damping silicone rubber the characteristics of voltage resistance and high damping. This application introduces organic molecules-inorganic molecules into the main chain of silicone rubber by modifying silica with a silane coupling agent. By destroying the regularity of the molecular chain, the low-temperature crystallization of silicone rubber is hindered, and the hysteresis loss of the movement of the macromolecular chain is increased, thereby reducing its crystallization temperature and glass transition temperature, and expanding the low-temperature application range of the polymer material.
[0030] (3) The butyl rubber added to the sound insulation material in this application is obtained by copolymerization of polyisobutylene and polyisoprene. The polyisobutylene chain segment has symmetrical methyl groups, and the isobutylene structural unit accounts for more than 97% of the macromolecule. The number of macromolecular chain substituents is large, the relaxation resistance of the chain segment is increased, the internal friction is large, and it has excellent damping performance. The modified silicone resin prepared in this application maintains stable damping performance in the full temperature range (within 100°C). DETAILED DESCRIPTION
[0031] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1 The preparation method of cross-linked silicone rubber comprises the following steps:
[0033] A1: 150 g of methyl vinyl phenyl silicone rubber (PVMQ, SE6635 silicone rubber produced by Momentive Advanced Materials Group, USA) and 4500 mL of chloroform were added to reactor A, stirred and dissolved, 120 g of m-chloroperbenzoic acid was added, and the mixture was kept at room temperature for 48 h, washed and dried to obtain component 1;
[0034] A2: Add 150g of component 1, 750mL of thioglycolic acid and 300mL of acid anhydride into reactor B and disperse evenly, add 3mL of concentrated sulfuric acid, control the temperature at 30°C, keep warm for 1h, wash and dry to obtain component 2;
[0035] A3: 150 g of nano-silicon dioxide, 2250 mL of anhydrous ethanol and 50 mL of deionized water were added to reactor C and dispersed evenly. The temperature was controlled at 60° C. 30 g of 3-(methacryloyloxy)propyltrimethoxysilane was added. Oxalic acid was added to adjust the pH to 3. The mixture was kept warm for 1 h, washed and dried to obtain component three.
[0036] A4: Add 150g of component 2, 45g of component 3 and 1500mL of chloroform into reactor D and disperse them evenly. Add 1.5g of triethylamine and react at room temperature for 1h. Wash and dry to obtain cross-linked silicone rubber.
[0037] Example 2 The preparation method of cross-linked silicone rubber comprises the following steps:
[0038] A1: 150 g of methyl vinyl phenyl silicone rubber (PVMQ, SE6635 silicone rubber produced by Momentive Advanced Materials Group, USA) and 7500 mL of chloroform were added to reactor A, stirred and dissolved, 120 g of m-chloroperbenzoic acid was added, and the mixture was kept at room temperature for 48 h, washed and dried to obtain component 1;
[0039] A2: Add 150g of component 1, 900mL of thioglycolic acid and 600mL of acid anhydride into reactor B and disperse evenly, add 3mL of concentrated sulfuric acid, control the temperature at 30°C, keep warm for 3h, wash and dry to obtain component 2;
[0040] A3: 150 g of nano-silicon dioxide, 2250 mL of anhydrous ethanol and 750 mL of deionized water were added to reactor C and dispersed evenly. The temperature was controlled at 70° C. 30 g of 3-(methacryloyloxy)propyltrimethoxysilane was added. Oxalic acid was added to adjust the pH to 3. The mixture was kept warm for 2 h, washed and dried to obtain component three.
[0041] A4: Add 150g of component 2, 45g of component 3 and 7500mL of chloroform into reactor D and disperse them evenly. Add 1.8g of triethylamine and react at room temperature for 1h. Wash and dry to obtain cross-linked silicone rubber.
[0042] Example 3 The preparation method of cross-linked silicone rubber comprises the following steps:
[0043] A1: 150 g of methyl vinyl phenyl silicone rubber (PVMQ, SE6635 silicone rubber produced by Momentive Advanced Materials Group, USA) and 8000 mL of chloroform were added to reactor A, stirred and dissolved, 120 g of m-chloroperbenzoic acid was added, and the mixture was kept at room temperature for 64 h, washed and dried to obtain component 1;
[0044] A2: Add 150g of component 1, 1500mL of thioglycolic acid and 750mL of acid anhydride into reactor B and disperse evenly, add 3mL of concentrated sulfuric acid, control the temperature at 35°C, keep warm for 3h, wash and dry to obtain component 2;
[0045] A3: 150 g of nano-silicon dioxide, 2250 mL of anhydrous ethanol and 50 mL of deionized water were added to reactor C and dispersed evenly. The temperature was controlled at 70° C. 75 g of 3-(methacryloyloxy)propyltrimethoxysilane was added. Oxalic acid was added to adjust the pH to 3. The mixture was kept warm for 3 h, washed and dried to obtain component three.
[0046] A4: Add 150g of component 2, 45g of component 3 and 8000mL of chloroform into reactor D and disperse them evenly. Add 2.25g of triethylamine and react at room temperature for 3h. Wash and dry to obtain cross-linked silicone rubber.
[0047] Embodiment 4 A production process of a new energy electric car sound insulation material comprises the following steps:
[0048] S1: 50g of butyl rubber (butyl rubber produced by Bayer AG, Germany, Mooney viscosity ML1+8 (125°C): 40-80, unsaturation: 0.16%-2.1%) was added to the roller of a rubber mixer, 2g of stearic acid and 3g of zinc oxide were added and mixed for 10min, 120g of the cross-linked silicone rubber prepared in Example 1 was added and mixed evenly, 2g of diisopropyl peroxide was added, and a thin film was formed, and film pressing and vulcanization molding were performed on a flat vulcanizer to obtain a modified silicone rubber; the modified silicone rubber and 3g of benzoyl peroxide were mixed for 6min to obtain a mixed component;
[0049] S2: The temperature of the open mill is set to 165°C for the front roller and 165°C for the rear roller, 100g of acrylonitrile-butadiene-styrene copolymer (ABS with the brand name PA-757 produced by Chi Mei Resin) is added to the plasticizing roll between the two rolls of the open mill, and 100g of the mixed components are added and mixed to obtain a masterbatch;
[0050] S3: 100 g of the masterbatch and 500 g of acrylonitrile-butadiene-styrene copolymer (ABS with the brand name PA-757 produced by Chi Mei Resin) were mixed evenly, melt-extruded, granulated, and dried to obtain a sound insulation material.
[0051] Embodiment 5 A production process of a new energy electric car sound insulation material comprises the following steps:
[0052] S1: 50g of butyl rubber (butyl rubber produced by Bayer AG, Germany, Mooney viscosity ML1+8 (125°C): 40-80, unsaturation: 0.16%-2.1%) was added to the roller of a rubber mixer, 2g of stearic acid and 3g of zinc oxide were added and mixed for 10min, 120g of the cross-linked silicone rubber prepared in Example 2 was added and mixed evenly, 2g of diisopropyl peroxide was added, and a thin film was formed, and film pressing and vulcanization molding were performed on a flat vulcanizer to obtain a modified silicone rubber; the modified silicone rubber and 3g of benzoyl peroxide were mixed for 6min to obtain a mixed component;
[0053] S2: The temperature of the open mill is set to 165°C for the front roller and 165°C for the rear roller, 100g of acrylonitrile-butadiene-styrene copolymer (ABS with the brand name PA-757 produced by Chi Mei Resin) is added to the plasticizing roll between the two rolls of the open mill, and 100g of the mixed components are added and mixed to obtain a masterbatch;
[0054] S3: 100 g of the masterbatch and 500 g of acrylonitrile-butadiene-styrene copolymer (ABS with the brand name PA-757 produced by Chi Mei Resin) were mixed evenly, melt-extruded, granulated, and dried to obtain a sound insulation material.
[0055] Embodiment 6 A production process of a new energy electric car sound insulation material comprises the following steps:
[0056] S1: 50g of butyl rubber (butyl rubber produced by Bayer AG, Germany, Mooney viscosity ML1+8 (125°C): 40-80, unsaturation: 0.16%-2.1%) was added to the roller of a rubber mixer, 2g of stearic acid and 3g of zinc oxide were added and mixed for 10min, 120g of the cross-linked silicone rubber prepared in Example 3 was added and mixed evenly, 2g of diisopropyl peroxide was added, and a thin film was formed, and film pressing and vulcanization molding were performed on a flat vulcanizer to obtain a modified silicone rubber; the modified silicone rubber and 3g of benzoyl peroxide were mixed for 6min to obtain a mixed component;
[0057] S2: The temperature of the open mill is set to 165°C for the front roller and 165°C for the rear roller, 100g of acrylonitrile-butadiene-styrene copolymer (ABS with the brand name PA-757 produced by Chi Mei Resin) is added to the plasticizing roll between the two rolls of the open mill, and 100g of the mixed components are added and mixed to obtain a masterbatch;
[0058] S3: 100 g of the masterbatch and 500 g of acrylonitrile-butadiene-styrene copolymer (ABS with the brand name PA-757 produced by Chi Mei Resin) were mixed evenly, melt-extruded, granulated, and dried to obtain a sound insulation material.
[0059] Comparative Example 1 The preparation method of cross-linked silicone rubber comprises the following steps:
[0060] A1: 10 g of methyl vinyl phenyl silicone rubber (PVMQ, SE6635 silicone rubber produced by Momentive Advanced Materials Group, USA) and 300 mL of chloroform were added to reactor A and stirred to dissolve, 8 g of m-chloroperbenzoic acid was added, and the mixture was kept at room temperature for 48 h, washed and dried to obtain component 1;
[0061] A2: 10 g of nano-silicon dioxide, 150 mL of anhydrous ethanol and 50 mL of deionized water were added to reactor C and dispersed evenly. The temperature was controlled at 60°C, 2 g of 3-(methacryloyloxy)propyltrimethoxysilane was added, and oxalic acid was added to adjust the pH to 3. The reaction was kept warm for 1 h, and then washed and dried to obtain component three.
[0062] A3: Blend 10 g of component 2 and 3 g of component 3 to obtain a cross-linked silicone rubber.
[0063] Comparative Example 2 The preparation method of cross-linked silicone rubber comprises the following steps:
[0064] A1: 10 g of nano-silicon dioxide, 150 mL of anhydrous ethanol and 50 mL of deionized water were added to reactor C and dispersed evenly. The temperature was controlled at 60°C, 2 g of 3-(methacryloyloxy)propyltrimethoxysilane was added, and oxalic acid was added to adjust the pH to 3. The mixture was kept warm for 1 h, washed and dried to obtain component three.
[0065] A2: 10 g of methyl vinyl phenyl silicone rubber (PVMQ, SE6635 silicone rubber produced by Momentive Advanced Materials Group, USA) and 3 g of the three components were blended to obtain a cross-linked silicone rubber.
[0066] Comparative Example 3 The preparation method of cross-linked silicone rubber comprises the following steps:
[0067] A1: 10 g of methyl vinyl phenyl silicone rubber (PVMQ, SE6635 silicone rubber produced by Momentive Advanced Materials Group, USA) and 300 mL of chloroform were added to reactor A and stirred to dissolve, 8 g of m-chloroperbenzoic acid was added, and the mixture was kept at room temperature for 48 h, washed and dried to obtain component 1;
[0068] A2: Add 10g of component 1, 50mL of thioglycolic acid and 20mL of acid anhydride into reactor B and disperse evenly, add 0.2mL of concentrated sulfuric acid, control the temperature at 30℃, keep warm for 1h, wash and dry, and obtain component 2;
[0069] A3: 10 g of nano-silicon dioxide, 150 mL of anhydrous ethanol and 50 mL of deionized water were added to reactor C and dispersed evenly. The temperature was controlled at 60°C, 2 g of 3-(methacryloyloxy)propyltrimethoxysilane was added, and oxalic acid was added to adjust the pH to 3. The mixture was kept warm for 1 h, washed and dried to obtain component three.
[0070] A4: Blend 10 g of component 2 and 3 g of component 3 to obtain a cross-linked silicone rubber.
[0071] Comparative Example 4 Compared with Example 4, Comparative Example 4 is only replaced by an equal amount of the cross-linked silicone rubber added in Example 4 with the cross-linked silicone rubber prepared in Comparative Example 1, and the other components and production process are completely the same as those in Example 4.
[0072] Comparative Example 5 Compared with Example 4, Comparative Example 5 is only that the cross-linked silicone rubber added in Example 4 is replaced by the cross-linked silicone rubber prepared in Comparative Example 2 in equal amount, and the other components and production process are completely the same as those in Example 4.
[0073] Comparative Example 6 Compared with Example 4, Comparative Example 6 is only replaced by an equal amount of the cross-linked silicone rubber added in Example 4 with the cross-linked silicone rubber prepared in Comparative Example 3, and the other components and production process are completely the same as those in Example 4.
[0074] Performance Testing
[0075] (1) Damping performance: The test was conducted using a Q800 dynamic thermomechanical analyzer produced by TA Corporation of the United States. The sample size was 4 mm × 12 mm × 3 mm, the heating rate was 2 °C / min, and the measurement temperature range was -80 °C to 185 °C. The test results are shown in Table 1.
[0076] Table 1: Statistical table of performance test data of Examples 1-3 and Comparative Examples 1-3
[0077] tanδmax Effective damping temperature range / (℃) △Ttanδ0.3、 / (℃) Example 1 0.83 -30~149 179 Example 2 0.88 -33~154 187 Example 3 0.85 -33~148 181 Comparative Example 1 0.71 -21~103 124 Comparative Example 2 0.63 -17~95 112 Comparative Example 3 0.77 -25~120 145
[0078] It can be seen from Table 1 that the maximum loss factor tanδmax of the cross-linked silicone rubber prepared in Examples 1-3 of the present application is ≥0.8, and the temperature range △Ttanδ0.3≥170°C within which the loss factor is greater than 0.3. The cross-linked silicone rubber prepared in the present application has the characteristics of high damping and a wide temperature range.
[0079] (2) Mechanical properties: tested according to GB / T 1040.2-2006 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics", the test results are shown in Table 2;
[0080] (3) Bending properties: Tested according to GB / T 9341-2008 “Determination of flexural properties of plastics”. The test results are shown in Table 2.
[0081] (4) Rockwell hardness: Tested in accordance with GB / T 3398.2-2008 "Plastics Hardness Determination Part 2: Rockwell Hardness". The test results are shown in Table 2.
[0082] Table 2: Statistical table of mechanical properties test data of Examples 4-6 and Comparative Examples 4-6
[0083] Tensile strength / (MPa) Bending strength / (MPa) <![CDATA[Impact strength / (kJ·cm -2 ).]]> Rockwell hardness Example 4 56.5 83.4 178.8 89 Example 5 57.8 84.5 179.4 85 Example 6 57.1 83.1 177.5 91 Comparative Example 4 44.1 62.1 165.2 88 Comparative Example 5 40.3 56.6 167.8 87 Comparative Example 6 49.8 67.9 169.9 89
[0084] As can be seen from Table 2, the sound insulation materials prepared in Examples 4-6 of the present application have excellent mechanical properties. By organically modifying silica with a silane coupling agent and using the modified silica as a "bridge" to perform organic cross-linking with silicone rubber and ABS, the phase separation phenomenon of silicone rubber, silica, etc. in the composite system is greatly reduced, and the sound insulation materials maintain excellent mechanical properties.
[0085] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A production process for sound insulation materials for new energy electric cars, characterized in that: The production process comprises the following steps: S1: After adding butyl rubber to the roller of a rubber mixer, adding stearic acid and zinc oxide for mixing, adding cross-linked silicone rubber for uniform mixing, adding dicumyl peroxide, thinning out sheets, vulcanizing and forming, and obtaining modified silicone rubber; after mixing the modified silicone rubber and benzoyl peroxide, obtaining a mixed component; S2: plasticizing the acrylonitrile-butadiene-styrene copolymer and rolling it, adding the mixed components and mixing them to obtain a masterbatch; S3: uniformly mixing the masterbatch and acrylonitrile-butadiene-styrene copolymer, melt-extruding, granulating, and drying to obtain a sound insulation material; The preparation method of the cross-linked silicone rubber comprises the following steps: A1: Add methyl vinyl phenyl silicone rubber and chloroform into reaction kettle A, stir and dissolve, add m-chloroperbenzoic acid, keep warm at room temperature for 48-64 hours, wash and dry to obtain component 1; A2: Add component 1, thioglycolic acid and acid anhydride into reactor B and disperse evenly, add concentrated sulfuric acid, control the temperature at 30-35°C, keep warm for 1-3h, wash and dry to obtain component 2; A3: Add nano-silicon dioxide, anhydrous ethanol and deionized water into reactor C and disperse them evenly, control the temperature at 60-70°C, add 3-(methacryloyloxy)propyltrimethoxysilane, adjust the pH to 3-5, keep the reaction warm for 1-3h, wash and dry to obtain component three; A4: Add component 2, component 3 and chloroform into reactor D and disperse them evenly. Add triethylamine and react at room temperature for 1-3 hours. Wash and dry to obtain cross-linked silicone rubber.
2. The production process of a new energy electric car sound insulation material according to claim 1 is characterized in that: The mass ratio of butyl rubber, stearic acid, zinc oxide, cross-linked silicone rubber, dicumyl peroxide and benzoyl peroxide in S1 is 50-100: 1-3: 1-5: 120: 0.5-2.5: 2.4-3.
6.
3. The production process of a new energy electric car sound insulation material according to claim 1 is characterized in that: The mass ratio of acrylonitrile-butadiene-styrene copolymer and mixed components in S2 is 1:1-1.
2.
4. The production process of a new energy electric car sound insulation material according to claim 1 is characterized in that: The mass ratio of the masterbatch to the acrylonitrile-butadiene-styrene copolymer in S3 is 1:4-8.
5. The production process of a new energy electric car sound insulation material according to claim 1 is characterized in that: The addition ratio of methyl vinyl phenyl silicone rubber, chloroform and m-chloroperbenzoic acid in A1 is 1g:30-100mL:0.4-0.8g.
6. The production process of a new energy electric car sound insulation material according to claim 1 is characterized in that: The addition ratio of component 1, thioglycolic acid, acid anhydride, and concentrated sulfuric acid in A2 is 1g: 5-10mL: 2-5mL: 0.01-0.02mL.
7. The production process of a new energy electric car sound insulation material according to claim 1 is characterized in that: The addition ratio of nano-silicon dioxide, anhydrous ethanol, deionized water, and 3-(methacryloyloxy)propyltrimethoxysilane in A3 is 10 g: 100-200 mL: 30-50 mL: 2-5 g.
8. The production process of a new energy electric car sound insulation material according to claim 1 is characterized in that: The addition ratio of component 2, component 3, chloroform and triethylamine in A4 is 1g: 0.1-0.3g: 10-100mL: 0.01-0.015g.
9. A sound insulation material for new energy electric cars, characterized in that: Made by the production process described in any one of claims 1-8.
Citation Information
Patent Citations
Methyl phenyl vinyl silicone rubber modified ABS (acrylonitrile butadiene styrene) soundproof material and preparation method thereof
CN104356583A
Graphene oxide modified anti-ageing agent, anti-thermo-oxidative-aging rubber containing graphene oxide modified anti-ageing agent and preparation method
CN110117390A